Industrial democracy conference, 1976 (London, 1976)
1976 1974-79 "Industrial democracy conference, 1976" [BW0192], 1976, Trades Union Congress Conference organised by the London Workers' Control Co-ordinating Committee, which was affiliated to the Institute for Workers' Control. During this period the Bullock Committee or Committee of Inquiry on Industrial Democracy was drafting proposals for legislation on workers' participation.